Polyols and Polyurethanes from the Liquefaction of Lignocellulosic Biomass. Issue 1 (16th December 2013) - Hu, Shengjun; Luo, Xiaolan; Li, Yebo
Abstract Polyurethanes (PUs), produced from the condensation polymerizations between polyols and isocyanates, are one of the most versatile polymer families. Currently, both polyols and isocyanates are largely petroleum derived. Recently, there have been extensive research interests in developing bio‐based polyols and PUs from renewable resources. As the world's most abundant renewable biomass, lignocellulosic biomass is rich in hydroxyl groups and has potential as a feedstock to produce bio‐based polyols and PUs. Lignocellulosic biomass can be converted to liquid polyols for PU applications through acid‐ or base‐catalyzed atmospheric liquefaction processes using polyhydric alcohols as liquefaction solvents. Biomass liquefaction‐derived polyols can be used to prepare various PU products, such as foams, films and adhesives. The properties of biomass liquefaction‐derived polyols and PUs depend on various factors, such as feedstock characteristics, liquefaction conditions, and PU formulations.